Natural history and description of Zatypota kerstinae sp.nov. (Hymenoptera: Ichneumonidae) reared from Theridion palmgreni Marusik et Tsellarius (Araneae: Theridiidae) in Finland - Fritzén, Niclas R. (Zootaxa, 2010)
Zatypota kerstinae sp. nov., belonging to the Polysphincta group of genera, is described. Its unusual cocoon is figured and a discussion on the natural history, the possible total distribution, the host range and the rarity of the new species is provided. Like all other species of the Polysphincta group of genera, the new species is a koinobiont ectoparasitoid of spiders. It has been reared from the theridiid Theridion palmgreni Marusik & Tsellarius, 1986 in Finland, collected mainly by beating lower branches of Norway spruce (Picea abies) in old forests. The results indicate that Z. kerstinae is univoltine with a very narrow realised host range consisting of a single species in Finland. Z. kerstinae seems to be a rare species in Finland, not only in entomological collections. Zatypota now comprises 7 species in Europe.